2017
DOI: 10.1021/acsbiomaterials.7b00021
|View full text |Cite
|
Sign up to set email alerts
|

Bioconjugation of Gold Nanobipyramids for SERS Detection and Targeted Photothermal Therapy in Breast Cancer

Abstract: Gold nanobipyramids (Au NBPs) with two sharp tips present an extremely strong electric field enhancement, which endows them with more advantages in biomedical photonics than other gold nanostructures. The application of Au NBPs for diagnosis and therapy is now under intensive investigation. Here, we report Au NBPs for surface-enhanced Raman scattering (SERS) detection and photothermal therapy (PTT) of MCF-7 cancer cells both in vitro and in vivo via bioconjugation with Raman reporter 2-naphthalenethiol (2-NAP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 40 publications
(51 reference statements)
1
70
0
Order By: Relevance
“…Furthermore, a new Au nanostructure (Au nanobipyramids) was reported to be applied for breast cancer detection and treatment in which Au nano-bipyramids were bio-conjugated with 2-naphthalenethiol and folic acid to target and kill human breast (adenocarcinoma) cells. 52 The authors revealed that the conjugated Au nano-bipyramids are capable of quantitative detection of the MCF-7 cells as well as enhancement of photothermal effect in vivo and in vitro.…”
Section: Au-based Nanomaterialsmentioning
confidence: 99%
“…Furthermore, a new Au nanostructure (Au nanobipyramids) was reported to be applied for breast cancer detection and treatment in which Au nano-bipyramids were bio-conjugated with 2-naphthalenethiol and folic acid to target and kill human breast (adenocarcinoma) cells. 52 The authors revealed that the conjugated Au nano-bipyramids are capable of quantitative detection of the MCF-7 cells as well as enhancement of photothermal effect in vivo and in vitro.…”
Section: Au-based Nanomaterialsmentioning
confidence: 99%
“…Current approaches of cancer detection by SERS focuses on sensing cancer‐related biomarkers and in vitro detection. Additionally, there are various studies which employ SERS to detect cancer by using both biomarkers and in vitro techniques (Feng et al, ; Huefner, Kuan, Barker, & Mahajan, ; Lee et al, ). However, most of the existing SERS probes are in the nanoscale size range which majorly influenced by several parameters such as size, surface chemistry, origin and type of cell (Austin, Kang, Yen, & El‐Sayed, ; Kang, Austin, & El‐Sayed, ; Song, Pu, Zhou, Duan, & Duan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus substituting GNRs for GBPs should be beneficial in some applications [5,6], e.g. for photodynamic and photothermal therapies [7] probes for bio-applications [8], detection of influenza virus [9], surface-enhanced Raman scattering detection [10], as well as cancer cell imaging and photodynamic therapies [11].…”
Section: Introductionmentioning
confidence: 99%